The irradiance fluctuations signal in atmospheric optical of systems transmit of informations - E.R. Milyutin (Физика волновых процессов и радиотехнические системы, 2016)
The turbulent atmosphere causes irradiance fluctuations for optical signals. Probability density function modeles to consider. Jnfluence of irradiance fluctuations of light background take iuto consideration.